Mechanism and enhancement of anti-parasitic-reaction catalytic activity of tungsten-carbide-coated graphite components for the growth of bulk GaN crystals. (1st April 2022) - Nakamura, Daisuke; Iida, Kazuyoshi; Horibuchi, Kayo; Aoki, Yuko; Takahashi, Naoko; Mori, Yuto; Moriyama, Miki; Nitta, Shugo; Amano, Hiroshi
Abstract: The working mechanism of the anti-parasitic-reaction (APR) catalyst of tungsten carbide (WC) coating on graphite in hydride vapor phase epitaxy GaN growth were examined. During NH3 annealing, the surface of WC is reduced as well as nitrided. The W2 N topmost layer was found to work as an APR-active catalyst to suppress the formation of GaN polycrystals during high-rate HVPE-GaN growth, while the regions covered with thick pyrolytic graphite residues were catalytically inert. The formation of an additional W2 C top layer on the WC underlayer was demonstrated to exhibit superior APR activity, i.e. complete suppression of GaN polycrystal formation.